2022
DOI: 10.1101/2022.04.21.22274060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of the neutralizing antibody sotrovimab among high-risk patients with mild to moderate SARS-CoV-2 in Qatar

Abstract: Effectiveness of sotrovimab against severe, critical, or fatal COVID-19 was investigated in Qatar using a case-control study design at a time when BA.2 Omicron subvariant dominated incidence. Adjusted odds ratio of progression to severe, critical, or fatal COVID-19, comparing those sotrovimab-treated to those untreated, was 2.67-fold higher (95% CI: 0.60-11.91).

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Despite evaluating a cohort predominantly infected with Omicron BA.1 sublineages, our findings do not fully support observed sotrovimab neutralization of BA.1 variants in vitro, [23] though perhaps a lower sotrovimab neutralization potency against Omicron/BA.1 and Omicron/BA.1.1 as compared to ancestral strains and prior variants of concern made our findings more predictable. [13,14] Further, with ineffective in vitro sotrovimab neutralization against Omicron BA.2 [13,14] and among newer Omicron subvariants, [24] as well as a clinical observation that sotrovimab did not mitigate disease progression during a BA.2 Omicron dominant phase, [15] our findings do support the statements by the NIH guidelines committee…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Despite evaluating a cohort predominantly infected with Omicron BA.1 sublineages, our findings do not fully support observed sotrovimab neutralization of BA.1 variants in vitro, [23] though perhaps a lower sotrovimab neutralization potency against Omicron/BA.1 and Omicron/BA.1.1 as compared to ancestral strains and prior variants of concern made our findings more predictable. [13,14] Further, with ineffective in vitro sotrovimab neutralization against Omicron BA.2 [13,14] and among newer Omicron subvariants, [24] as well as a clinical observation that sotrovimab did not mitigate disease progression during a BA.2 Omicron dominant phase, [15] our findings do support the statements by the NIH guidelines committee…”
Section: Discussionsupporting
confidence: 85%
“…Despite evaluating a cohort predominantly infected with Omicron BA.1 sublineages, our findings do not fully support observed sotrovimab neutralization of BA.1 variants in vitro ,[23] though perhaps a lower sotrovimab neutralization potency against Omicron/BA.1 and Omicron/BA.1.1 as compared to ancestral strains and prior variants of concern made our findings more predictable. [13, 14] Further, with ineffective in vitro sotrovimab neutralization against Omicron BA.2 [13, 14] and among newer Omicron subvariants,[24] as well as a clinical observation that sotrovimab did not mitigate disease progression during a BA.2 Omicron dominant phase, [15] our findings do support the statements by the NIH guidelines committee [25] and FDA [26] that sotrovimab should not be recommended as a current outpatient treatment against COVID-19 among the general population of outpatients that meet EUA criteria. However, with a signal towards potential sotrovimab benefit in patients ≥ 65 years old, immunosuppressed, or with multiple comorbid conditions, some consideration should be given towards continued treatment in highest risk individuals depending on the availability of alternate treatments options, particularly if these observations continue to be made in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study in Qatar conducted during the reported Omicron BA.2 wave found nonsignificant higher odds (OR 2.67, 95% CI 0.60–11.91) of progression to severe, critical, or fatal COVID-19 in sotrovimab-treated patients compared with those untreated [ 17 ]. However, patients were excluded from the control group if they showed signs or symptoms of severe COVID-19 within 7 days of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Up to February 27, 2023, seven of the 14 studies were published in an international peer-reviewed journal, [26][27][28][29][30][31][32] and seven were published as pre-prints. [33][34][35][36][37][38][39] Three of the preprints have since been published in a peer-reviewed journal .…”
Section: Study Characteristicsmentioning
confidence: 99%